2013
DOI: 10.1093/nar/gkt1353
|View full text |Cite
|
Sign up to set email alerts
|

Models that include supercoiling of topological domains reproduce several known features of interphase chromosomes

Abstract: Understanding the structure of interphase chromosomes is essential to elucidate regulatory mechanisms of gene expression. During recent years, high-throughput DNA sequencing expanded the power of chromosome conformation capture (3C) methods that provide information about reciprocal spatial proximity of chromosomal loci. Since 2012, it is known that entire chromatin in interphase chromosomes is organized into regions with strongly increased frequency of internal contacts. These regions, with the average size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 38 publications
(89 reference statements)
10
109
0
Order By: Relevance
“…In our model, we show that TADs emerge without requiring such specific interactions; any two regions of sticky monomers separated by a nonsticky linker would form TADs. Another study proposed that transcription-induced supercoiling may be responsible for the formation of TADs (Benedetti et al 2014). Although this model is consistent with our observation that sites of active transcription demarcate TAD boundaries, there is limited evidence that supercoiling of chromatinized DNA exists in Drosophila and other organisms.…”
Section: Discussionsupporting
confidence: 91%
“…In our model, we show that TADs emerge without requiring such specific interactions; any two regions of sticky monomers separated by a nonsticky linker would form TADs. Another study proposed that transcription-induced supercoiling may be responsible for the formation of TADs (Benedetti et al 2014). Although this model is consistent with our observation that sites of active transcription demarcate TAD boundaries, there is limited evidence that supercoiling of chromatinized DNA exists in Drosophila and other organisms.…”
Section: Discussionsupporting
confidence: 91%
“…These matrices are broadly used in biophysical experiments to determine the 3D organisation of genetic material of eukaryotes [34][35][36][37][38] and bacteria 4,39 . As in the case presented here, although on a much more complex level, characteristic patterns seem to emerge 35 , and their understanding is one of the major challenges in the field of biophysics.…”
Section: Patterns In the Contact Maps Reveal Loops And Branchesmentioning
confidence: 99%
“…By using dynamic simulations, it was shown that including supercoiling into models of topological domain organization can qualitatively and quantitatively reproduce experimental 3C data obtained in eukaryotic cells. 93 Another work points to supercoiling and transcriptional activity as critical determinants of domain formation in bacteria. It was revealed that bacterial genome is composed of regions with increased frequency of contacts, highly reminiscent of topological domains in eukaryotic chromosomes.…”
Section: Dna Topology and Genome Architecturementioning
confidence: 99%